SPEECH DISCOURSE AT THE FIFTH PROTEST "SERBIA AGAINST VIOLENCE" IN BELGRADE - Handan, Arijana (Political Review, 2024)
The "Serbia Against Violence" protests lasted for several months during 2023 and were triggered by two mass murders that occurred in May 2023. The protests were first civil at the beginning, but in the later period a part of the opposition parties would be involved. During the period when they were civil, they were attended by public figures such as actors Svetlana Bojković and Dragan Bjelogrlić and television hosts Ivan Ivanović and Zoran Kesić. This analysis also includes speeches of "ordinary people", who were given the opportunity to speak as "victims of the current government regime in Serbia". Therefore, this paper analyses what discourse was dominant in their speeches: such as the young, beaten farmer who did not want to sell his land; the son of Stanka Gligorijević, who was killed in the car accident in which Zoran Babić was... The method used in the research is discourse analysis. Speeches that can be found on the YouTube channel of the cable television "N1", which continuously broadcasted those protests, were analysed in this research. This analysis shows that a pathetic style with elements of sarcasm and political-ideology dominated.